NIKOLAI NIKOLAEVICH SIDELNIKOV’S CHORAL CYCLE “ROMANCERO OF LOVE AND DEATH”: A STYLISTIC AND DRAMATURGICAL ANALYSIS. (Multidisciplinary Journal of Science and Technology, 2026)
The present study examines Nikolai Nikolaevich Sidelnikov’s choral cycle “Romancero of Love and Death” based on poems by Federico García Lorca as an integral artistic phenomenon within the context of Russian music of the late twentieth century. The research focuses on the dramaturgical structure of the cycle, the composer’s intonational thinking, and the methods of musical interpretation of poetic texts through choral writing. Genre-related, rhythmic, textural, and timbral features of the composition are analyzed, with particular attention given to its symbolic imagery built on the opposition between love and death. The study reveals the synthetic nature of the cycle, combining elements of national color, neo-folkloristic tendencies, and contemporary compositional techniques. The conclusions contribute to a deeper understanding of Sidelnikov’s choral legacy and may be applied in both scholarly research and performance practice.